2018
DOI: 10.1111/1365-2656.12872
|View full text |Cite
|
Sign up to set email alerts
|

Personalities influence spatial responses to environmental fluctuations in wild fish

Abstract: Although growing evidence supports the idea that animal personality can explain plasticity in response to changes in the social environment, it remains to be tested whether it can explain spatial responses of individuals in the face of natural environmental fluctuations. This is a major challenge in ecology and evolution as spatial dynamics link individual‐ and population‐level processes.In this study, we investigated the potential of individual personalities to predict differences in fish behaviour in the wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 41 publications
5
46
1
Order By: Relevance
“…Externally determining sex is not possible for gray triggerfish, so we were unable to examine potential differences in movement rates between males and females. Recent research suggests variability in animal personalities like boldness or shyness can explain individual differences in movement behaviors (Villegas-Ríos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Externally determining sex is not possible for gray triggerfish, so we were unable to examine potential differences in movement rates between males and females. Recent research suggests variability in animal personalities like boldness or shyness can explain individual differences in movement behaviors (Villegas-Ríos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Shyer animals are often characterized by high responsiveness to change (Coppens et al, 2010;Wolf et al, 2008), and indeed, in our boldness test, shy individuals were more responsive to the presentation of a novel object. Previous work has linked boldness with responsiveness to environmental change: for instance, shy, but not bold, Atlantic cod (Gadus morhua) adjust their home ranges in response to increases in sea temperature (Villegas-Ríos, Réale, Freitas, Moland, & Olsen, 2018), and in sleepy lizards (Tiliqua rugosa), shy individuals were more responsive to changes in resource availability (Spiegel et al, 2015). During incubation, when birds are less constrained to return to predictable foraging sites, shy individuals may therefore be more likely to select sites based on environmental cues, rather than based on previous foraging attempts.…”
Section: Boldness and Foraging Site Fidelitymentioning
confidence: 99%
“…Some pioneering studies on repeatability of behavior demonstrated that spatial ecology traits such as home range are repeatable in aquatic species like burbot (Lota lota; Harrison et al, 2015) and cod (Gadus morhua, Villegas-Ríos, Reale, Freitas, Moland, & Olsen, 2017; Villegas-Ríos, Réale, Freitas, Moland, & Olsen, 2018), and other studies revealed the repeatability of behavior in decapods based on laboratory assays (e.g., Gherardi, Aquiloni, & Tricarico, 2012). With this background, our last hypothesis is that spatial behavioral traits of lobster are repeatable, and thus, selection on behavioral traits has the potential to fuel evolutionary changes.…”
mentioning
confidence: 99%